Electrode mixture, electrode, and secondary battery
By adding polycarboxylic acids and non-fluoropolymers to the electrode mixture, the problem of increasing viscosity of the electrode mixture is solved, the uniformity and high density of the electrode material layer are achieved, and the performance and stability of the electrode are improved.
Patent Information
- Application Number
- CN202380054242.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-18
- Publication Date
- 2025-03-04
AI Technical Summary
The viscosity of the existing electrode mixture is prone to increase during use, which makes it difficult to control the thickness and density of the electrode material layer, affecting the stability and performance of the electrode.
The electrode mixture is prepared by adding polycarboxylic acid and a non-fluoropolymer containing unsaturated monocarboxylic acid units to the electrode mixture, thereby inhibiting the increase in viscosity and improving the adhesion between the electrode material layer and the current collector.
The stability of the viscosity of the electrode mixture is achieved, the uniformity and high density of the electrode material layer are ensured, and the performance and stability of the electrode are improved.
Smart Images

Figure BDA0005245049700000041 
Figure BDA0005245049700000161 
Figure BDA0005245049700000181
Abstract
Description
Technical Field
[0001] The invention relates to an electrode mixture, an electrode and a secondary battery. Background Art
[0002] Patent document 1 describes a positive electrode mixture for a non-aqueous battery, which is obtained by adding 0.5 to 10 parts by weight of an organic acid relative to 100 parts by weight of a conductive aid to a mixture comprising a positive electrode active material, a conductive aid, a binder and an organic solvent, wherein the positive electrode active material comprises a composite metal oxide, the conductive aid comprises high-structure carbon black, and the binder comprises a ternary or higher fluorine-based copolymer containing at least vinylidene fluoride, tetrafluoroethylene and a flexibility-modified fluorine-containing monomer.
[0003] Patent document 2 describes a slurry for an electrode mixture of a lithium secondary battery, which is a slurry for an electrode mixture of a lithium secondary battery containing an electrode active material (A), a binder (B) and an organic solvent (C). The slurry for the electrode mixture is characterized in that the binder (B) contains: (B1) a fluorine-containing polymer represented by a composition formula (B1); and (B2) a solvent-soluble thermoplastic resin other than the fluorine-containing polymer (B1).
[0004] Composition formula (B1):
[0005] (VDF) m (TFE) n (HFP) l
[0006] (Wherein, VDF is a structural unit derived from vinylidene fluoride; TFE is a structural unit derived from tetrafluoroethylene; HFP is a structural unit derived from hexafluoropropylene; 0.45≤m≤1; 0.05≤n≤0.5; 0≤l≤0.1. Wherein, m+n+l=1.)
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2009 / 063907
[0010] Patent Document 2: International Publication No. 2010 / 092977 Summary of the invention
[0011] Problems to be solved by the invention
[0012] An object of the present invention is to provide an electrode mixture having both a property of being less likely to change in viscosity and a property of being able to form an electrode material layer that is closely attached to a current collector with high peel strength in a balanced manner.
[0013] Means for solving problems
[0014] According to the present invention, an electrode mixture is provided, which is an electrode mixture containing a binder (A), an electrode active material (B) and an additive (C), wherein the binder (A) comprises a fluorine-containing polymer containing vinylidene fluoride units, and the additive (C) comprises a polycarboxylic acid (C1) and a non-fluorine-containing polymer (C2) containing an unsaturated monocarboxylic acid unit.
[0015] Effects of the Invention
[0016] According to the present invention, it is possible to provide an electrode mixture having both a property of being less likely to change in viscosity and a property of being able to form an electrode material layer that is closely attached to a current collector with high peel strength in a balanced manner. DETAILED DESCRIPTION
[0017] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0018] Patent document 1 states that by adding a small amount of organic acid, floating when a positive electrode mixture containing high-structure carbon black as a conductive aid is coated on a current collector can be effectively prevented, and cracking when a thick positive electrode mixture layer is formed by drying can be effectively prevented. In addition, patent document 2 states that a solvent-soluble thermoplastic resin plays a role in improving adhesion to the current collector.
[0019] But, if use these previous technologies to prepare electrode mixture, it can be known that along with the passage of time, the viscosity of electrode mixture rises.If after the preparation electrode mixture, the viscosity of electrode mixture rises gradually, then be difficult to control the thickness, the density of the electrode material layer formed by using electrode mixture, there is the problem that is difficult to stably manufacture the electrode with the electrode material layer of desired formation.
[0020] Therefore, in-depth research has been conducted on means to solve this problem. As a result, it was found that by adding polycarboxylic acids and non-fluorinated polymers containing unsaturated monocarboxylic acid units to the electrode mixture, the increase in the viscosity of the electrode mixture after the electrode mixture is prepared is suppressed, and further, the adhesion of the formed electrode material layer to the collector is improved.
[0021] That is, the electrode mixture of the present invention is an electrode mixture containing a binder (A), an electrode active material (B) and an additive (C), wherein the additive (C) comprises a polycarboxylic acid (C1) and a non-fluorinated polymer (C2) containing an unsaturated monocarboxylic acid unit. Each component is described in detail below.
[0022] (Binder (A))
[0023] The binder (A) used in the present invention comprises a fluorine-containing polymer containing vinylidene fluoride units (VdF).
[0024] The fluorine-containing polymer may be a VdF homopolymer consisting of only VdF units, or a polymer containing VdF units and other monomer units. As other monomers, any monomer that can copolymerize with VdF may be a fluorinated monomer (excluding VdF) or a non-fluorinated monomer.
[0025] Examples of the fluorinated monomer (excluding VdF) include tetrafluoroethylene (TFE), vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropylene, and trans-1,3,3,3-tetrafluoropropylene.
[0026] The fluoroalkyl vinyl ether is preferably a fluoroalkyl vinyl ether having a fluoroalkyl group having 1 to 5 carbon atoms, and more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether).
[0027] As the fluorinated monomer, from the perspective of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, it is preferred to select at least one from the group consisting of TFE, CTFE, 2,3,3,3-tetrafluoropropylene, HFP and fluoroalkyl vinyl ether, more preferably at least one from the group consisting of TFE and HFP, and particularly preferably TFE.
[0028] The fluorinated monomer (excluding VdF) may or may not have a polar group.
[0029] Examples of the non-fluorinated monomer include non-fluorinated monomers having no polar group such as ethylene and propylene, and non-fluorinated monomers having a polar group (hereinafter sometimes referred to as a polar group-containing monomer).
[0030] If a monomer with a polar group is used as a non-fluorinated monomer, the polar group is introduced into a fluoropolymer, thereby, an electrode material layer that is closely attached to the current collector with a higher peel strength can be formed. As a polar group, at least one of the groups consisting of a carbonyl-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfuric acid group, a phosphoric acid group, an amino group, an amide group and an alkoxy group is preferably selected, more preferably at least one of the groups consisting of a carbonyl-containing group, an epoxy group and a hydroxyl group, and further preferably a carbonyl-containing group. The above-mentioned hydroxyl group does not include a hydroxyl group that constitutes a part of the above-mentioned carbonyl-containing group. In addition, the above-mentioned amino group is a univalent functional group after removing hydrogen from ammonia, a primary amine or a secondary amine.
[0031] The carbonyl-containing group is a functional group having a carbonyl group (-C(=O)-). As the carbonyl-containing group, a group represented by the general formula: -COOR (R represents a hydrogen atom, an alkyl group or a hydroxyalkyl group) or a carboxylic anhydride group is preferred, and a group represented by the general formula: -COOR is more preferred. The number of carbon atoms of the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and further preferably 1 to 3. As the group represented by the general formula: -COOR, specifically, -COOCH 2 CH 2 OH, -COOCH 2 CH(CH 3 )OH、-COOCH(CH 3 )CH 2 OH, -COOH, -COOCH 3 ,-COOC 2 H 5 When the group represented by the general formula: -COOR is -COOH or includes -COOH, -COOH may be a carboxylate such as a metal carboxylate or an ammonium carboxylate.
[0032] In addition, the carbonyl-containing group may be a group represented by the general formula: -X-COOR (X is an atomic group with a molecular weight of 500 or less and a main chain consisting of 1 to 20 atoms, and R represents a hydrogen atom, an alkyl group or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3.
[0033] As the above-mentioned amide group, preferably, a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group or a substituted or unsubstituted phenyl group).
[0034] Examples of the polar group-containing monomer include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonates such as dimethyl methylenemalonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylates such as succinic acid acryloxyethyl succinate, succinic acid acryloxyethyl phthalate, and methacrylic acid acryloxyethyl phthalate; and monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; General formula (A1):
[0035] [Chemistry 1]
[0036]
[0037] (Where R 1 , R 2 and R 3 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. X represents a single bond or an atomic group having a molecular weight of 500 or less and a main chain composed of 1 to 20 atoms. Y represents an inorganic cation and / or an organic cation. ) represented by the monomer (A1); etc.
[0038] It should be noted that, in the present invention, "(meth)acrylic acid" refers to any one of acrylic acid and methacrylic acid. The "(meth)" in the names of other compounds shall be interpreted in the same manner. In addition, the number of atoms in the main chain of the atomic group is the number of atoms in the straight chain skeleton portion, and the oxygen atoms constituting the carbonyl group and the hydrogen atoms constituting the methylene group are not included in the number of atoms in the main chain. For example, in the case where the monomer (A1) is acryloyloxyethyl phthalate, the straight chain skeleton portion is -C-OCCO-C-CC-, and its number of atoms is 8.
[0039] As the polar group-containing monomer, a monomer (A1) represented by the general formula (A1) is preferred because it can provide an electrode mixture whose viscosity is less likely to change and can form an electrode material layer that is closely attached to the current collector with higher peel strength.
[0040] In the general formula (A1), Y represents an inorganic cation and / or an organic cation. Examples of inorganic cations include cations of H, Li, Na, K, Mg, Ca, Al, Fe, etc. Examples of organic cations include NH 4 NH 3 R 5 NH 2 R 5 2 、NHR 5 3 NR 5 4 (R 5 Y is preferably H, Li, Na, K, Mg, Ca, Al, NH 4 , more preferably H, Li, Na, K, Mg, Al, NH 4 , H, Li, Al, NH 4 , and H is particularly preferred. It should be noted that, for the sake of convenience, specific examples of inorganic cations and organic cations are described with symbols and valences omitted.
[0041] In the general formula (A1), R 1 ~R 3R independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. The alkyl group is preferably a methyl group or an ethyl group. 1 and R 2 R 3 Preferred is a hydrogen atom or a methyl group.
[0042] In the general formula (A1), X is a single bond or an atomic group having a molecular weight of 500 or less and a main chain composed of 1 to 20 atoms. The atomic group is preferably a hydrocarbon group having 1 to 8 carbon atoms, a heteroatom, or an atomic group having a molecular weight of 500 or less and a main chain containing at least one heteroatom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, and a phosphorus atom.
[0043] The hydrocarbon group is a divalent hydrocarbon group. The number of carbon atoms of the above hydrocarbon group is preferably 4 or less. As the above hydrocarbon group, alkylene groups and alkenylene groups having the above carbon number can be cited, among which at least one selected from the group consisting of methylene, ethylene, ethylidene, propylidene and isopropylidene is preferred, and at least one selected from the group consisting of methylene and ethylene is more preferred.
[0044] When X is a hetero atom, the hetero atom is preferably at least one selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom and a phosphorus atom, and more preferably an oxygen atom.
[0045] When X is an atomic group, an oxygen atom is preferably used as a heteroatom in the atomic group.
[0046] When X is an atomic group, the side chain represented by the general formula: -X-COOY in the general formula (A1) is preferably any of the following.
[0047] General formula: -CO-R 6 - Side chain shown by COOY
[0048] (Where R 6 It represents an atomic group having a molecular weight of 472 or less and having a main chain with 1 to 19 atoms. Y is as described above.)
[0049] General formula: -OR 7 - Side chain shown by COOY
[0050] (Where R 7 It represents an atomic group having a molecular weight of 484 or less and having a main chain with 1 to 19 atoms. Y is as described above.)
[0051] General formula: -COO-R 8 -The side chain represented by COOY,
[0052] (R 8It is an atomic group with a molecular weight of 456 or less and a main chain containing 1 to 18 atoms. Y is as described above.)
[0053] When X is an atomic group, examples of the monomer (A1) include (meth)acrylamide compounds such as N-carboxyethyl (meth)acrylamide; thio(meth)acrylate compounds such as carboxyethyl thio(meth)acrylate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl, succinic acid methacrylic acid ethyl, succinic acid acryloxypropyl, succinic acid methacrylic acid propyl, phthalic acid acryloxyethyl, phthalic acid methacrylic acid ethyl; etc. When X is an atomic group, examples of the monomer (A1) include 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl, succinic acid methacrylic acid ethyl, succinic acid acryloxypropyl, succinic acid methacrylic acid propyl, succinic acid methacrylic acid propyl, etc. When X is an atomic group, examples of the monomer (A1) include 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl, succinic acid methacrylic acid ethyl, succinic acid acryloxypropyl, succinic acid methacrylic acid propyl.
[0054] As the monomer (A1), a monomer (A1) in which X in the general formula (A1) is a single bond or a hydrocarbon group having 1 to 8 carbon atoms is preferred.
[0055] As monomer (A1), from the perspective of obtaining an electrode mixture that is less likely to change viscosity and can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, it is more preferred to select at least one from the group consisting of (meth)acrylic acid and its salts, vinylacetic acid (3-butenoic acid) and its salts, 3-pentenoic acid and its salts, 4-pentenoic acid and its salts, 3-hexenoic acid and its salts, 4-heptenoic acid and its salts, and 5-hexenoic acid and its salts, and (meth)acrylic acid and its salts are further preferred.
[0056] The content of the polar group-containing monomer unit in the fluorinated polymer is preferably 0.05 to 2.0 mol %, more preferably 0.10 mol % or more, further preferably 0.25 mol % or more, particularly preferably 0.40 mol % or more, and more preferably 1.5 mol % or less, based on all monomer units.
[0057] In the present specification, the content of the polar group-containing monomer unit in the fluorinated polymer can be measured by acid-base titration of the acid group when the polar group is an acid group such as carboxylic acid.
[0058] As the other monomer, at least one selected from the group consisting of TFE, CTFE, (meth)acrylic acid, 2,3,3,3-tetrafluoropropylene, HFP and fluoroalkyl vinyl ether is preferred. (Meth)acrylic acid includes acrylic acid and methacrylic acid.
[0059] The content of other monomer units in the fluorinated polymer is preferably 0.0001 mol% to 50.0 mol%, more preferably 0.01 mol% or more, further preferably 0.10 mol% or more, more preferably 45.0 mol% or less, further preferably 40.0 mol% or less, particularly preferably 35.0 mol% or less, based on all monomer units.
[0060] When the fluorinated polymer contains other monomer units, the content of the VdF unit of the fluorinated polymer is 50.0 mol% to 99.9999 mol% relative to all monomer units, more preferably 55.0 mol% or more, further preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 99.99 mol% or less, further preferably 99.90 mol% or less.
[0061] When the fluorinated polymer contains a fluorinated monomer unit as another monomer unit, the content of the fluorinated monomer unit is preferably 0.0001 mol% to 50.0 mol%, more preferably 2.0 mol% or more, further preferably 3.0 mol% or more, particularly preferably 4.0 mol% or more, more preferably 45.0 mol% or less, further preferably 40.0 mol% or less, particularly preferably 35.0 mol% or less, relative to all monomer units.
[0062] When the fluorinated polymer contains a fluorinated monomer unit as another monomer unit, the content of the VdF unit of the fluorinated polymer is 50.0 mol% to 99.999 mol% relative to all monomer units, more preferably 55.0 mol% or more, further preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 98.0 mol% or less, further preferably 97.0 mol% or less, particularly preferably 96.0 mol% or less.
[0063] When the fluorinated polymer contains non-fluorinated monomer units such as polar group-containing monomers as other monomer units, the content of the non-fluorinated monomer units is preferably 0.0001 mol% to 50.0 mol%, more preferably 0.01 mol% or more, further preferably 0.10 mol% or more, more preferably 5.0 mol% or less, further preferably 3.0 mol% or less, particularly preferably 1.5 mol% or less, relative to all monomer units.
[0064] When the fluorinated polymer contains a non-fluorinated monomer unit as another monomer unit, the content of the VdF unit of the fluorinated polymer is preferably 50.0 mol% to 99.999 mol% relative to all monomer units, more preferably 95.0 mol% or more, further preferably 97.0 mol% or more, particularly preferably 98.5 mol% or more, more preferably 99.99 mol% or less, further preferably 99.90 mol% or less.
[0065] In the present invention, the composition of the fluorine-containing polymer can be, for example, 19 In addition, when the fluorine-containing polymer contains a monomer unit containing a polar group as another monomer unit, the content of the monomer unit containing a polar group, for example, when the polar group is an acid group such as a carboxylic acid, can be measured by acid-base titration of the acid group.
[0066] The weight average molecular weight (in terms of polystyrene) of the fluorinated polymer is preferably 10,000 to 3,000,000, more preferably 30,000 or more, further preferably 50,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, further preferably 2,200,000 or less, particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0067] In one embodiment of the electrode mixture, the fluorinated polymer containing vinylidene fluoride units contained by the binder (A) can be polyvinylidene fluoride. In the present invention, polyvinylidene fluoride refers to a fluorinated polymer containing 98.0 mol% or more of VdF units relative to all monomer units. Polyvinylidene fluoride can be a VdF homopolymer consisting only of VdF units, or a polymer containing VdF units and other monomer units. As other monomers, as long as they are monomers that can copolymerize with VdF, they can be fluorinated monomers (wherein, excluding VdF) or non-fluorinated monomers. As other monomers, the above-mentioned monomers can be used.
[0068] As other monomers constituting polyvinylidene fluoride, at least one selected from the group consisting of CTFE, fluoroalkyl vinyl ether, HFP, 2,3,3,3-tetrafluoropropylene and the monomer (A1) represented by the general formula (A1) is preferred. In addition, polyvinylidene fluoride preferably does not contain TFE units.
[0069] The content of other monomer units in polyvinylidene fluoride is 0 to 2.0 mol %, preferably 0 to 1.5 mol %, and more preferably 0 to 1.0 mol % based on all monomer units.
[0070] The content of the VdF unit in the polyvinylidene fluoride is 98.0 mol % or more, preferably 98.5 mol % or more, more preferably 99.0 mol % or more, and preferably 100 mol % or less, based on all monomer units.
[0071] The weight average molecular weight (in terms of polystyrene) of polyvinylidene fluoride is preferably 50,000 to 3,000,000, more preferably 80,000 or more, further preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, further preferably 2,200,000 or less, particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0072] As polyvinylidene fluoride, from the aspect of obtaining an electrode mixture that is less likely to change in viscosity and can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, it is preferred to select at least one of the group consisting of a fluoropolymer consisting only of vinylidene fluoride units, a fluoropolymer containing vinylidene fluoride units and fluorinated monomer units (wherein vinylidene fluoride units are not included), and a fluoropolymer containing vinylidene fluoride units and units of a monomer (A1) based on the general formula (A1). From the aspect of an excellent balance between a low rate of change in viscosity and high adhesion of the electrode material layer, it is more preferred to select at least one of the group consisting of a fluoropolymer consisting only of vinylidene fluoride units and a fluoropolymer containing vinylidene fluoride units and fluorinated monomer units (wherein vinylidene fluoride units are not included).
[0073] In one embodiment of the electrode mixture, the binder (A) contains a fluorinated copolymer. In the present invention, the fluorinated copolymer refers to a fluorinated polymer containing less than 98.0 mol% of VdF units relative to all monomer units. Therefore, the fluorinated copolymer is a polymer containing VdF units and other monomer units. As other monomers, as long as they are monomers that can copolymerize with VdF, they can be fluorinated monomers (wherein, VdF is not included) or non-fluorinated monomers. As other monomers, the above-mentioned monomers can be used.
[0074] As other monomers constituting the fluorinated copolymer, among them, fluorinated monomers (excluding VdF) are preferred, at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether, CTFE and 2,3,3,3-tetrafluoropropylene is more preferred, and TFE is further preferred.
[0075] The content of other monomer units in the fluorinated copolymer is preferably 43.0 mol% or less, more preferably 40.0 mol% or less, further preferably 37.0 mol% or less, and exceeds 2.0 mol%, preferably 3.0 mol% or more, more preferably 5.0 mol% or more, further preferably 10.0 mol% or more, based on all monomer units.
[0076] The content of the VdF unit in the fluorinated copolymer is preferably 57.0 mol% or more, more preferably 60.0 mol% or more, further preferably 63.0 mol% or more, and less than 98.0 mol%, preferably 97.0 mol% or less, more preferably 95.0 mol% or less, further preferably 90.0 mol% or less, based on all monomer units.
[0077] The fluorinated copolymer may also contain the above-mentioned polar group-containing monomer units. The content of the polar group-containing monomer units of the fluorinated copolymer is preferably 0.05 mol% to 2.0 mol% relative to the total monomer units, more preferably 0.10 mol% or more, further preferably 0.25 mol% or more, particularly preferably 0.40 mol% or more, and more preferably 1.5 mol% or less.
[0078] The weight average molecular weight (in terms of polystyrene) of the fluorinated copolymer is preferably 50,000 to 3,000,000, more preferably 80,000 or more, further preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, further preferably 2,200,000 or less, particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0079] Examples of the fluorine-containing copolymer include VdF / TFE copolymer, VdF / HFP copolymer, VdF / TFE / HFP copolymer, VdF / TFE / (meth)acrylic acid copolymer, VdF / HFP / (meth)acrylic acid copolymer, VdF / CTFE copolymer, VdF / TFE / 4-pentenoic acid copolymer, VdF / TFE / 3-butenoic acid copolymer, VdF / TFE / HFP / (meth)acrylic acid copolymer, VdF / TFE / HFP / 4-pentenoic acid copolymer, VdF / TFE / HFP / 3-butenoic acid copolymer, VdF / TFE / 2-carboxyethyl acrylate copolymer, VdF / TFE / HFP / 2-carboxyethyl acrylate copolymer, VdF / TFE / acryloyloxyethyl succinate copolymer, and VdF / TFE / HFP / acryloyloxyethyl succinate copolymer.
[0080] Among them, the fluorinated copolymer is preferably at least one selected from the group consisting of VdF / TFE copolymers, VdF / HFP copolymers, VdF / fluoroalkyl vinyl ether copolymers, VdF / CTFE copolymers and VdF / 2,3,3,3-tetrafluoropropylene copolymers, and more preferably VdF / TFE copolymers.
[0081] The VdF / TFE copolymer contains VdF units and TFE units. By using the VdF / TFE copolymer as the fluorine-containing copolymer, an electrode mixture whose viscosity is less likely to change can be obtained.
[0082] The content of the VdF unit is preferably 57.0 mol % or more, more preferably 60.0 mol % or more, and further preferably 63.0 mol % or more, and is preferably less than 98.0 mol %, more preferably 90.0 mol % or less, and further preferably 85.0 mol % or less, relative to all monomer units of the VdF / TFE copolymer.
[0083] The content of TFE units is preferably more than 2.0 mol %, more preferably 10.0 mol % or more, further preferably 15.0 mol % or more, and is preferably 43.0 mol % or less, more preferably 40.0 mol % or less, further preferably 37.0 mol % or less, relative to all monomer units of the VdF / TFE copolymer.
[0084] In addition to the VdF unit and the TFE unit, the VdF / TFE copolymer may also include units based on monomers copolymerizable with VdF and TFE (wherein, VdF and TFE are not included). The content of the units based on monomers copolymerizable with VdF and TFE is preferably 3.0 mol% or less relative to the total monomer units of the VdF / TFE copolymer.
[0085] Examples of monomers copolymerizable with VdF and TFE include the above-mentioned fluorinated monomers, the above-mentioned non-fluorinated monomers, etc. As monomers copolymerizable with VdF and TFE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, and at least one selected from the group consisting of HFP, 2,3,3,3-tetrafluoropropylene and monomer (A1) is more preferred.
[0086] The weight average molecular weight (polystyrene equivalent) of the VdF / TFE copolymer is preferably 50,000 to 2,000,000, more preferably 80,000 or less, further preferably 100,000 or less, more preferably 1,700,000 or more, further preferably 1,500,000 or more. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0087] In one embodiment of the electrode mixture, the binder (A) contains polyvinylidene fluoride and a fluorinated copolymer. When the binder (A) contains polyvinylidene fluoride and a fluorinated copolymer, changes in the viscosity of the electrode mixture can be further suppressed.
[0088] In the electrode mixture, from the perspective of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, the mass ratio of polyvinylidene fluoride to the fluorine-containing copolymer (polyvinylidene fluoride / fluorine-containing copolymer) is preferably 99 / 1 to 1 / 99, more preferably 97 / 3 or less, further preferably 95 / 5 or less, further preferably 90 / 10 or less, more preferably 3 / 97 or more, further preferably 5 / 95 or more, further preferably 10 / 90 or more.
[0089] The content of the binder (A) in the electrode mixture is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, preferably 0.1% by mass or more, more preferably 0.5% by mass or more relative to the mass of the solid component in the electrode mixture. By making the content of the binder (A) within the above range, an electrode mixture in which the viscosity is less likely to change and an electrode material layer that is closely attached to the collector with a higher peel strength can be obtained.
[0090] (Electrode active material (B))
[0091] The electrode active material used in the present invention may be a positive electrode active material or a negative electrode active material.
[0092] As the positive electrode active material, a substance capable of electrochemically entrapping and releasing lithium ions can be used, preferably a lithium composite oxide, more preferably a lithium transition metal composite oxide. As the above-mentioned positive electrode active material, a lithium-containing transition metal phosphate compound is also preferred. The above-mentioned positive electrode active material is also preferably a substance containing lithium and at least one transition metal, such as a lithium transition metal composite oxide and a lithium-containing transition metal phosphate compound.
[0093] As the transition metal of the lithium transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As a specific example of the lithium transition metal composite oxide, LiCoO 2 Lithium·Cobalt composite oxides; LiNiO 2 Lithium nickel composite oxide; LiMnO 2 、LiMn 2 O 4 , Li 2 MnO 3Lithium-manganese composite oxides such as lithium-nickel-manganese composite oxides; materials obtained by replacing part of the transition metal atoms that are the main body of these lithium-transition metal composite oxides with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. Examples of the materials obtained by the above replacement include lithium-nickel-manganese composite oxides, lithium-nickel-cobalt-aluminum composite oxides, lithium-nickel-cobalt-manganese composite oxides, lithium-manganese-aluminum composite oxides, and lithium-titanium composite oxides. More specifically, LiNi 0.5 Mn 0.5 O 2 、LiNi 0.85 Co 0.10 Al 0.05 O 2 、LiNi 0.33 Co 0.33 Mn 0.33 O 2 、LiNi 0.5 Mn 0.3 Co 0.2 O 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 、LiNi 0.8 Mn 0.1 Co 0.1 O 2 、LiMn 1.8 Al 0.2 O 4 、LiMn 1.5 Ni 0.5 O 4 , Li 4 Ti 5 O 12 、LiNi 0.82 Co 0.15 Al 0.03 O 2 wait.
[0094] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples of the lithium-containing transition metal phosphate compound, for example, LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 、LiFeP 2 O 7 Iron phosphates such as LiCoPO 4Cobalt phosphates, etc.; substances obtained by replacing part of the transition metal atoms serving as the main body of these lithium transition metal phosphate compounds with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0095] In particular, LiCoO is preferred from the perspectives of high voltage, high energy density, or charge-discharge cycle characteristics. 2 、LiNiO 2 、LiMn 2 O 4 、LiNi 0.82 Co 0.15 Al 0.03 O 2 、LiNi 0.33 Mn 0.33 Co 0.33 O 2 、LiNi 0.5 Mn 0.3 Co 0.2 O 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 、LiNi 0.8 Mn 0.1 Co 0.1 O 2 、LiFePO 4 .
[0096] In addition, as the electrode active material (B), preferably, a lithium metal oxide represented by the general formula (B1) is used.
[0097] General formula (B1): LiNi Z M (1-Z) O 2
[0098] (In the formula, z satisfies 0.5≤z<1, and M is at least one selected from the group consisting of Co, Mn, and Al.)
[0099] In the general formula (B1), z is a coefficient satisfying 0.5≤z<1, and preferably 0.6≤z<1, and more preferably 0.7≤z≤0.9, in order to obtain a secondary battery with a higher capacity. The viscosity of the electrode mixture of the present invention is not easily changed even when a lithium metal oxide containing a large amount of Ni is used as the electrode active material (B).
[0100] As the lithium metal oxide represented by the general formula (B1), it is preferred to be selected from the group consisting of LiNi 0.80 Co 0.15 Al 0.05O 2 、LiNi 0.82 Co 0.15 Al 0.03 O 2 、LiNi 0.5 Mn 0.3 Co 0.2 O 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 、LiNi 0.8 Mn 0.1 Co 0.1 O 2 and LiNi 0.90 Mn 0.05 Co 0.05 O 2 At least one selected from the group consisting of LiNi 0.82 Co 0.15 Al 0.03 O 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 and LiNi 0.8 Mn 0.1 Co 0.1 O 2 At least one of the group consisting of.
[0101] In addition, a substance having a different composition from the substance constituting the main positive electrode active material may be attached to the surface of these positive electrode active materials, and the positive electrode active material obtained thereby may be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and the like.
[0102] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, the following methods: a method of dissolving or suspending the substance in a solvent, adding the substance to the positive electrode active material by infiltration and drying; a method of dissolving or suspending the surface-attached substance precursor in a solvent, adding the substance to the positive electrode active material by infiltration and then reacting the substance by heating or the like; a method of adding the substance to the positive electrode active material precursor and simultaneously firing the substance; and the like.
[0103] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and further preferably 10 ppm or more, as a lower limit, relative to the positive electrode active material, and preferably 20% or less, more preferably 10% or less, and further preferably 5% or less as an upper limit. The surface-attached substance can inhibit the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material, and can improve the battery life; however, if the amount of its attachment is too small, its effect cannot be fully demonstrated; if the amount of its attachment is too large, it will hinder the entry and exit of lithium ions, so the resistance may increase.
[0104] The shape of the positive electrode active material particles uses the previously used block, polyhedron, spherical, ellipsoidal, plate-like, needle-like, columnar, etc., wherein it is preferred that the primary particles are condensed to form secondary particles, and the shape of the secondary particles is spherical or ellipsoidal. Usually in electrochemical elements, along with its charging and discharging, the active material in the electrode expands and shrinks, so it is easy to cause the destruction of the active material or the disconnection of the conductive path caused by its stress. Therefore, compared with the single particle active material of only primary particles, the material formed by the aggregation of primary particles to form secondary particles can alleviate the stress of expansion and contraction and prevent degradation, so it is preferred. In addition, compared with the particles of plate-like equiaxial orientation, the orientation of the electrode during molding is less in the case of spherical or ellipsoidal particles, so the expansion and contraction of the electrode during charging and discharging is also less, and it can also be evenly mixed in the mixing with the conductive agent when making the electrode, so it is preferred.
[0105] The tap density of the positive electrode active material is usually 1.3 g / cm 3 Above, preferably 1.5 g / cm 3 More preferably, 1.6 g / cm 3 More than, most preferably 1.7g / cm 3 Above. If the tap density of the positive electrode active material is less than the above lower limit, the amount of dispersion medium required when the positive electrode material layer is formed increases, and the required amount of conductive agent and copolymer increases. Sometimes the filling rate of the positive electrode active material in the positive electrode material layer will be limited, and the battery capacity will be limited. By using metal composite oxide powders with high tap density, a high-density positive electrode material layer can be formed. The larger the tap density is, the better. There is no particular upper limit. However, if it is too large, the diffusion of lithium ions in the positive electrode material layer using non-aqueous electrolyte as a medium becomes rate-limiting, and sometimes the load characteristics are easily reduced. Therefore, it is usually 2.5g / cm 3 Below, preferably 2.4 g / cm 3 the following.
[0106] The tap density of the positive electrode active material was determined by passing the sample through a sieve with a mesh size of 300 μm and dropping the sample to a depth of 20 cm. 3The powder is placed in a tapping cell and filled to the capacity. A powder density meter (e.g. Tap Denser manufactured by Seishin Enterprise) is then used to perform 1000 oscillations with a stroke length of 10 mm. The density is calculated from the volume and weight of the sample at this time and is defined as the tap density.
[0107] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter in the case where the primary particles are agglomerated to form secondary particles) is usually 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and most preferably 3 μm or more; usually 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. If it is less than the above lower limit, a high bulk density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, which may cause a decrease in battery performance, or when the positive electrode of the battery is made, that is, the active material and the conductive agent, copolymer, etc. are made into a slurry using a solvent and applied in a thin film, stripes and other problems may sometimes occur. Here, by mixing two or more positive electrode active materials with different median diameters d50, the filling property during the production of the positive electrode can be further improved.
[0108] It should be noted that the median diameter d50 in the present invention is measured using a known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as the dispersion medium used during measurement, a 0.1% by mass sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the measured refractive index is set to 1.24 for measurement.
[0109] In the case where the primary particles are condensed to form secondary particles, the average primary particle size of the positive electrode active material is usually 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, and most preferably 0.1 μm or more; usually 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics sometimes increases. On the contrary, if it is less than the lower limit, it is usually sometimes due to poor reversibility of charge and discharge due to underdeveloped crystallization. It should be noted that the primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph with a magnification of 10,000 times, the longest value of the slice generated by the left and right boundary lines of the primary particles relative to the straight line in the horizontal direction is obtained for any 50 primary particles, and the average value is taken to obtain the primary particle size.
[0110] The BET specific surface area of the positive electrode active material is 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 / g or above; 4.0m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease; if the BET specific surface area is larger than this range, the tap density is difficult to increase, and the coating property during the formation of the positive electrode material layer is sometimes prone to problems.
[0111] The BET specific surface area is defined as follows: Using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), pre-dry the sample at 150°C for 30 minutes under nitrogen flow, and then use a nitrogen-helium mixed gas accurately adjusted to a relative pressure of 0.3 relative to atmospheric pressure to perform the measurement by the nitrogen adsorption BET single-point method based on the gas flow method, and use the obtained value to define the BET specific surface area.
[0112] As a method for producing the positive electrode active material, a common method for producing an inorganic compound is used. In particular, various methods are considered for producing a spherical or ellipsoidal active material, for example, the following method can be cited: a transition metal raw material such as a transition metal nitrate or sulfate and a raw material of other elements as necessary are dissolved or crushed and dispersed in a solvent such as water, the pH is adjusted under stirring, a spherical precursor is produced and recovered, and it is dried as needed, and then LiOH, Li 2 CO 3 、LiNO 3 A method for obtaining an active material by calcining a Li source at a high temperature; dissolving or crushing a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, oxide, and other raw materials of other elements as necessary in a solvent such as water, drying and forming them by a spray dryer to form a spherical or elliptical spherical precursor, and adding LiOH, Li 2 CO 3 、LiNO 3 A method for obtaining an active material by calcining a transition metal source such as a transition metal nitrate, sulfate, hydroxide, oxide, etc. with LiOH, Li 2 CO 3 、LiNO 3 A method in which a raw material such as a Li source and, if necessary, other elements are dissolved or crushed and dispersed in a solvent such as water, dried and molded using a spray dryer to form a spherical or ellipsoidal precursor, and fired at a high temperature to obtain an active material; etc.
[0113] It should be noted that in the present invention, a single type of positive electrode active material can be used alone, or two or more positive electrode active material powders with different compositions or different powder physical properties can be used in any combination and proportion.
[0114] When the electrode binder of the present invention contains a positive electrode active material, the content of the binder is preferably 0.01 to 5.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0115] As the negative electrode active material, a negative electrode active material that exhibits a potential of 2.5 V or less based on Li when alloyed with Li or combined with Li can be cited.
[0116] As the negative electrode active material, a negative electrode active material containing a metal can be used. The metal contained in the negative electrode active material is usually a metal that can be electrochemically alloyed with an alkali metal such as Li or Na.
[0117] As the negative electrode active material, elemental metals such as Si, Zn, Sn, W, Al, Sb, Ge, Bi, and In that can be electrochemically alloyed with Li can be cited; alloys containing Si, Zn, Sn, W, Al, Sb, Ge, Bi, and In; lithium alloys such as lithium aluminum alloy and lithium tin alloy; metal oxides such as tin oxide and silicon oxide; and lithium titanate. As the negative electrode active material, one or more of them can be used.
[0118] As the negative electrode active material, a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti is preferably used, more preferably Si (elemental Si), an oxide of Si, an alloy containing Si, Sn (Sn carrier), an oxide of Sn, and an alloy containing Sn, and further preferably at least one selected from the group consisting of Si and SiO x (0 < x < 2).
[0119] In addition, as the negative electrode active material, a carbonaceous material such as graphite powder can also be used. The carbonaceous material can be used together with the negative electrode active material containing a metal. Examples of the carbonaceous material include natural graphite, artificial carbonaceous materials, artificial graphite materials, thermal decomposition products of organic substances such as carbonaceous materials {such as natural graphite, coal-based coke, petroleum-based coke, coal-based asphalt, petroleum-based asphalt, or substances obtained by oxidation treatment of these asphalts, needle coke, pitch coke and carbon materials obtained by partially graphitizing them, furnace black, acetylene black, Ketjen black, asphalt-based carbon fibers, etc., organic substances that can be carbonized (such as coal tar pitch from soft asphalt to hard asphalt, or coal-based heavy oils such as dry distillation liquefied oil, straight-run heavy oils such as atmospheric residual oil and vacuum residual oil, decomposed petroleum heavy oils such as ethylene tar produced as a by-product during thermal decomposition of crude oil, naphtha, etc., and aromatic hydrocarbons such as acenaphthylene, decacyclic ene, anthracene, phenanthrene, N-ring compounds such as phenazine or acridine, thiophene, bithiophene, etc. S-ring compounds, biphenyl, terphenyl and other polyphenyls, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, insolubilized products of these substances, nitrogen-containing organic polymers such as polyacrylonitrile and polypyrrole, sulfur-containing organic polymers such as polythiophene and polystyrene, natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan, and sucrose, thermoplastic resins such as polyphenylene sulfide and polyphenylene ether, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin) and their carbides, or solutions obtained by dissolving carbonizable organic matter in low molecular weight organic solvents such as benzene, toluene, xylene, quinoline, and n-hexane, and their carbides} carbonaceous materials obtained by heat treatment at a temperature in the range of 400°C to 3200°C one or more.
[0120] When the negative electrode mixture contains a metal-containing negative electrode active material and a carbonaceous material, the mass ratio of the metal-containing negative electrode active material to the carbonaceous material is preferably 1 / 99 to 99 / 1, more preferably 5 / 95 to 95 / 5, and even more preferably 10 / 10 to 90 / 10.
[0121] When the electrode mixture of the present invention contains a negative electrode active material, the content of the binder is preferably 0.01 to 20.0 parts by mass, more preferably 0.1 to 10.0 parts by mass, based on 100 parts by mass of the negative electrode active material.
[0122] In order to increase the capacity of the obtained electrode, the content of the electrode active material (positive electrode active material or negative electrode active material) is preferably 40% by mass or more in the solid content of the electrode mixture.
[0123] In the electrode mixture of the present invention, from the perspective of obtaining an electrode mixture that can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, the mass ratio (A / B) of the binder (A) to the electrode active material (B) is preferably 0.01 / 99.99 to 10 / 90, more preferably 0.5 / 99.5 or more, further preferably 1 / 99 or more, more preferably 4 / 96 or less, and further preferably 3 / 97 or less.
[0124] (Conductive agent)
[0125] The electrode mixture may further contain a conductive agent. Examples of the conductive agent include carbon blacks such as acetylene black and Ketjen black, carbon materials such as graphite, carbon fibers, carbon nanotubes, carbon nanohorns, and graphene.
[0126] The content of the conductive agent is preferably 0.001 to 10 parts by mass, more preferably 0.01 to 2.0 parts by mass, based on 100 parts by mass of the electrode active material.
[0127] (Additive (C))
[0128] The electrode mixture of the present invention comprises a polycarboxylic acid (C1) and a non-fluorinated polymer (C2) containing an unsaturated monocarboxylic acid unit as an additive (C). By adding the polycarboxylic acid (C1) and the non-fluorinated polymer (C2) to the electrode mixture, the viscosity change rate of the electrode mixture can be reduced. Furthermore, by adding the polycarboxylic acid (C1) and the non-fluorinated polymer (C2) to the electrode mixture, an electrode material layer having a high peeling strength with the collector can be formed compared to an electrode material layer formed by an electrode mixture containing only any one of the polycarboxylic acid (C1) and the non-fluorinated polymer (C2).
[0129] The polycarboxylic acid (C1) is a compound having two or more carboxyl groups in the molecule, and may be a saturated polycarboxylic acid or an unsaturated polycarboxylic acid. The polycarboxylic acid (C1) is preferably a dicarboxylic acid, and more preferably an unsaturated dicarboxylic acid.
[0130] As the polycarboxylic acid (C1), from the perspective of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, it is preferred to select at least one of the group consisting of tartaric acid, citric acid, oxalic acid, malonic acid, maleic acid, citraconic acid, succinic acid, adipic acid, phthalic acid, isophthalic acid and terephthalic acid, and tartaric acid is more preferred.
[0131] The non-fluorinated polymer (C2) is a polymer containing no fluorine atoms but containing unsaturated monocarboxylic acid units. In the present invention, the unsaturated monocarboxylic acid refers to a compound containing no fluorine atoms and having one or more unsaturated bonds and one carboxyl group in the molecule, and examples thereof include a compound having one (meth)acryloyl group and one carboxyl group in the molecule.
[0132] As the unsaturated monocarboxylic acid, a monomer (C2) represented by the general formula (C2) is preferred from the viewpoint of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is closely attached to the current collector with a higher peel strength.
[0133] General formula (C2):
[0134] [Chemistry 2]
[0135]
[0136] (Where R 1 , R 2 and R 3 Each is independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. X is an atomic group having a molecular weight of 500 or less and having a single bond or a main chain consisting of 1 to 20 atoms. Y is an inorganic cation and / or an organic cation.
[0137] As R in the general formula (C2) 1 ~R 3 , X and Y may be any of the following: 1 ~R 3 , X and Y are the same substances, preferably the same substances.
[0138] As the monomer (C2), a monomer (C2) in which X in the general formula (C2) is a single bond or a hydrocarbon group having 1 to 8 carbon atoms is preferred, and a monomer (C2) in which X is a single bond is more preferred.
[0139] As the monomer (C2), (meth)acrylic acid and its salts are preferred from the viewpoint of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is closely attached to the current collector with higher peel strength. That is, as the non-fluorinated polymer (C2), poly(meth)acrylic acid is preferred.
[0140] The non-fluorinated polymer (C2) may contain unsaturated monocarboxylic acid units and non-fluorinated monomer units (but excluding unsaturated monocarboxylic acid units). As the non-fluorinated monomer, the substances exemplified as the non-fluorinated monomers that can be contained in the fluorinated polymer as the binder (A) can be exemplified.
[0141] The content of the unsaturated monocarboxylic acid unit in the non-fluorinated polymer (C2) is preferably 90.0 mol% or more, more preferably 95.0 mol% or more, further preferably 99.0 mol% or more, particularly preferably 99.9 mol% or more, and is preferably 100 mol% or less, based on all monomer units.
[0142] The content of the non-fluorinated monomer units in the non-fluorinated polymer (C2) is preferably 10.0 mol% or less, more preferably 5.0 mol% or less, further preferably 1.0 mol% or less, particularly preferably 0.1 mol% or less, and preferably 0 mol% or more, based on all monomer units.
[0143] The number average molecular weight of the non-fluorinated polymer (C2) is preferably 1500000 or less, more preferably 1000000 or less, further preferably 500000 or less, preferably 3000 or more, more preferably 50000 or more, further preferably 100000 or more. If the number average molecular weight is high, homogenization of the electrode mixture slurry may become difficult from the solubility point of view, and if the molecular weight is too low, the viscosity of the electrode mixture slurry may become low.
[0144] From the perspective of obtaining an electrode mixture whose viscosity is less likely to change and which can form an electrode material layer that is tightly bonded to the collector with a higher peel strength, the mass ratio of the polycarboxylic acid (C1) to the non-fluorinated polymer (C2) ((C1) / (C2)) is preferably 1 / 99 to 99 / 1, more preferably 3 / 97 or more, further preferably 6 / 94 or more, further preferably 9 / 91 or more, particularly preferably 15 / 85 or more, more preferably 97 / 3 or less, further preferably 94 / 6 or less, further preferably 91 / 9 or less, and particularly preferably 85 / 15 or less.
[0145] In particular, when the mass ratio ((C1) / (C2)) of the polycarboxylic acid (C1) to the non-fluorinated polymer (C2) is 15 / 85 to 85 / 15, an electrode mixture having a viscosity that is less likely to change and an electrode material layer that is closely attached to the current collector with a higher peel strength can be obtained. The mass ratio ((C1) / (C2)) is most preferably 20 / 80 or more, and most preferably 80 / 20 or less.
[0146] The content of the additive (C) in the electrode mixture is preferably 0.01% by mass to 5.0% by mass relative to the mass of the binder (A) and the electrode active material (B) in the electrode mixture, more preferably below 3.0% by mass, further preferably below 2.5% by mass, particularly preferably below 2.0% by mass. By making the content of the additive (C) be the above range, it is possible to obtain an electrode mixture in which the viscosity is less likely to change and the electrode material layer that is closely attached to the collector with higher peel strength can be formed.
[0147] (Solvent)
[0148] The electrode mixture of the present invention preferably contains a solvent. Examples of the solvent include organic solvents.
[0149] Examples of the organic solvent include nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; chain carbonate solvents such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, butyl butyrate, and ethyl acetate; cyclic carbonates such as ethylene carbonate, propylene carbonate, and 4-fluoro-1,3-dioxolane-2-one; ether solvents such as tetrahydrofuran and dioxane; β-alkoxypropionamides such as β-methoxy-N,N-dimethylpropionamide, β-n-butoxy-N,N-dimethylpropionamide, and β-n-hexyloxy-N,N-dimethylpropionamide; phosphates such as triethyl phosphate and trimethyl phosphate; and low-boiling-point general-purpose organic solvents such as mixed solvents thereof.
[0150] As the organic solvent, a solvent represented by the general formula (1) can also be used.
[0151] General formula (1):
[0152] [Chemistry 3]
[0153]
[0154] (Where R 11 , R 12 and R 13 are independently H or a monovalent substituent, wherein R 11 , R 12 and R 13 The total number of carbon atoms is 6 or more, R 11 , R 12 and R 13 At least one of R is an organic group having a carbonyl group. 11 , R 12 and R 13 Any two of them can be bonded to form a ring. )
[0155] As the solvent represented by the general formula (1), it is preferred that at least one selected from the group consisting of 3-methoxy-N,N-dimethylpropionamide, N-ethyl-2-pyrrolidone (NEP), N-butyl-2-pyrrolidone (NBP), acryloylmorpholine, N-cyclohexyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 3-butoxy-N,N-dimethylpropionamide, N,N,N',N'-tetraethyl urea, N,N-dimethylacetoacetamide, N-octyl-2-pyrrolidone and N,N-diethylacetamide.
[0156] As the solvent, from the viewpoint of excellent coating properties, at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and a solvent represented by the general formula (1) is preferred.
[0157] More preferably, at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, N-ethyl-2-pyrrolidone (NEP), N-butyl-2-pyrrolidone (NBP), acryloylmorpholine, N-cyclohexyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 3-butoxy-N,N-dimethylpropionamide, N,N,N',N'-tetraethylurea, N,N-dimethylacetoacetamide, N-octyl-2-pyrrolidone and N,N-diethylacetamide is used.
[0158] More preferably, at least one selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, N-ethyl-2-pyrrolidone and N-butyl-2-pyrrolidone,
[0159] In particular, at least one selected from the group consisting of N-methyl-2-pyrrolidone and N,N-dimethylacetamide is preferred.
[0160] In the electrode mixture of the present invention, the content of the solvent is determined by considering the coating property of the collector, the film forming property after drying, etc. In the electrode mixture of the present invention, the total content of the binder (A) and the electrode active material (B) is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 85% by mass, and further preferably 65% by mass to 80% by mass in the solid content of the electrode mixture. In addition, in the electrode mixture of the present invention, the total content of the additive (C) and the solvent is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 40% by mass, and further preferably 20% by mass to 35% by mass.
[0161] In the electrode mixture of the present invention, the solid content concentration is preferably 95% by mass or less, more preferably 90% by mass or less, and is preferably 50% by mass or more, more preferably 60% by mass or more.
[0162] From the aspect that coating is easy and it is easy to obtain the positive electrode material layer with the desired thickness, the viscosity of the electrode mixture is preferably 1000mPa·s to 80000mPa·s, more preferably 3000mPa·s or more, further preferably 5000mPa·s or more, more preferably 70000mPa·s or less, further preferably 60000mPa·s or less. The above viscosity can be measured at 25°C using a B-type viscometer.
[0163] The electrode mixture of the present invention can be an electrode mixture for secondary batteries or an electrode mixture for lithium ion secondary batteries. In addition, the electrode mixture of the present invention can be a positive electrode mixture for making a positive electrode or a negative electrode mixture for making a negative electrode, but is preferably a positive electrode mixture.
[0164] (electrode)
[0165] The electrode of the present invention comprises a current collector and an electrode material layer. The electrode material layer is formed using the electrode mixture of the present invention and can be arranged on one side or both sides of the current collector. The electrode of the present invention can be a positive electrode having a positive electrode material layer or a negative electrode having a negative electrode material layer.
[0166] The density of the electrode material layer is preferably 1.5 g / cm 3 ~5.0g / cm 3 , more preferably 2.0 g / cm 3 ~4.5g / cm 3 .
[0167] The density of the electrode material layer can be calculated from the mass and volume of the electrode material layer.
[0168] In order to obtain higher battery characteristics, the thickness of the electrode material layer is preferably 20 μm or more, more preferably 30 μm or more, further preferably 40 μm or more, particularly preferably 45 μm or more, preferably 170 μm or less, more preferably 150 μm or less. In addition, the thickness of the electrode material layer can be 85 μm or less, or less than 69 μm.
[0169] The thickness of the electrode material layer can be measured with a micrometer. When the electrode material layer is provided on both sides of the current collector, the thickness of the electrode material layer in the present invention is the thickness per single side.
[0170] Examples of the current collector included in the electrode of the present invention include metal foils and metal meshes made of iron, stainless steel, copper, aluminum, nickel, titanium, and the like, and aluminum foil is preferred.
[0171] The electrode of the present invention can be suitably produced by a production method in which the electrode mixture of the present invention is applied to a current collector. After the electrode mixture is applied, the coating film can be further dried and the obtained dry coating film can be pressed.
[0172] The coating amount of the electrode mixture on the current collector is preferably 10 mg / cm 2 More preferably, 17.5 mg / cm 2 Above, preferably 60 mg / cm 2 Less than 50 mg / cm 2The coating amount of the electrode mixture is the dry weight of the electrode mixture per unit area.
[0173] (Secondary battery)
[0174] Furthermore, according to the present invention, there is provided a secondary battery including the above-mentioned electrode.
[0175] The electrode material layer formed from the electrode mixture of the present invention may be a positive electrode material layer or a negative electrode material layer.
[0176] The secondary battery of the present invention preferably comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein one or both of the positive electrode and the negative electrode are the above-mentioned electrodes. In addition, the secondary battery of the present invention preferably comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode is the above-mentioned electrode. In addition, a separator may be sandwiched between the positive electrode and the negative electrode.
[0177] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate can be used. The electrolyte can also use a conventionally known electrolyte, and LiClO can be used. 4 、LiAsF 6 、LiPF 6 , LiBF 4 、LiCl、LiBr、CH 3 SO 3 Li, CF 3 SO 3 Li, cesium carbonate, etc.
[0178] The electrode of the present invention can be suitably used as an electrode for a wound-type secondary battery. In addition, the secondary battery of the present invention may be a wound-type secondary battery.
[0179] The electrode of the present invention can be used not only in the lithium ion secondary battery using a liquid electrolyte as described above as a non-aqueous electrolyte secondary battery, but also in a polymer electrolyte lithium secondary battery. In addition, it is also useful as an electric double layer capacitor.
[0180] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0181] <1> According to a first aspect of the present invention, there is provided an electrode mixture comprising a binder (A), an electrode active material (B) and an additive (C), wherein:
[0182] The binder (A) comprises a fluorine-containing polymer containing vinylidene fluoride units,
[0183] The additive (C) comprises a polycarboxylic acid (C1) and a non-fluorine-containing polymer (C2) containing an unsaturated monocarboxylic acid unit.
[0184] <2> According to the second aspect of the present invention, an electrode mixture based on the first aspect is provided, wherein the polycarboxylic acid (C1) is at least one selected from the group consisting of tartaric acid, citric acid, oxalic acid, malonic acid, maleic acid, citraconic acid, succinic acid, adipic acid, phthalic acid, isophthalic acid and terephthalic acid.
[0185] <3> According to a third aspect of the present invention, there is provided the electrode mixture according to the first aspect or the second aspect, wherein the polycarboxylic acid (C1) is tartaric acid.
[0186] <4> According to a fourth aspect of the present invention, there is provided the electrode mixture according to any one of the first to third aspects, wherein the unsaturated monocarboxylic acid unit is a unit based on a monomer (C2) represented by the general formula (C2).
[0187] General formula (C2):
[0188] [Chemistry 4]
[0189]
[0190] (Where R 1 , R 2 and R 3 Each is independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. X is an atomic group having a molecular weight of 500 or less and having a single bond or a main chain consisting of 1 to 20 atoms. Y is an inorganic cation and / or an organic cation.
[0191] <5> According to a fifth aspect of the present invention, there is provided the electrode mixture according to any one of the first to fourth aspects, wherein the non-fluorinated polymer (C2) is polyacrylic acid.
[0192] <6> According to a sixth aspect of the present invention, there is provided the electrode mixture according to any one of the first to fifth aspects, wherein the content of the additive (C) is 0.01% by mass to 5.0% by mass relative to the mass of the binder (A) and the electrode active material (B).
[0193] <7> According to a seventh aspect of the present invention, there is provided the electrode mixture according to any one of the first to sixth aspects, wherein the mass ratio ((C1) / (C2)) of the polycarboxylic acid (C1) to the non-fluorinated polymer (C2) is 9 / 91 to 91 / 9.
[0194] <8> According to an eighth aspect of the present invention, there is provided the electrode mixture according to any one of the first to seventh aspects, wherein the binder (A) comprises, as the fluorine-containing polymer, polyvinylidene fluoride containing 98.0 mol % or more of vinylidene fluoride units.
[0195] <9> According to the 9th aspect of the present invention, an electrode mixture based on the 8th aspect is provided, wherein the polyvinylidene fluoride is at least one selected from the group consisting of a fluorinated polymer consisting only of vinylidene fluoride units, a fluorinated polymer containing vinylidene fluoride units and fluorinated monomer units (wherein, vinylidene fluoride units are not included), and a fluorinated polymer containing vinylidene fluoride units and units based on a monomer (A1) represented by the general formula (A1).
[0196] General formula (A1):
[0197] [Chemistry 5]
[0198]
[0199] (Where R 1 , R 2 and R 3 Each is independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. X is an atomic group having a molecular weight of 500 or less and having a single bond or a main chain consisting of 1 to 20 atoms. Y is an inorganic cation and / or an organic cation.
[0200] <10> According to a tenth aspect of the present invention, there is provided the electrode mixture according to the eighth aspect or the ninth aspect, wherein the binder (A) further comprises a fluorinated copolymer containing less than 98.0 mol % of vinylidene fluoride units.
[0201] <11> According to the 11th aspect of the present invention, there is provided an electrode mixture based on the 10th aspect, wherein the fluorinated copolymer is a fluorinated copolymer containing vinylidene fluoride units and fluorinated monomer units (wherein, vinylidene fluoride units are not included), and the fluorinated monomer units are at least one selected from the group consisting of tetrafluoroethylene units, hexafluoropropylene units, fluoroalkyl vinyl ether units, chlorotrifluoroethylene units and 2,3,3,3-tetrafluoropropylene units.
[0202] <12> According to a twelfth aspect of the present invention, there is provided the electrode mixture according to any one of the first to eleventh aspects, wherein the electrode active material (B) contains a lithium composite oxide.
[0203] <13> According to a 13th aspect of the present invention, there is provided the electrode mixture according to any one of the 1st to 12th aspects, wherein the electrode active material (B) contains a lithium metal oxide represented by the general formula (B1).
[0204] General formula (B1): LiNiZ M (1-Z) O 2
[0205] (In the formula, z satisfies 0.5≤z<1, and M is at least one selected from the group consisting of Co, Mn, and Al.)
[0206] <14> According to a 14th aspect of the present invention, there is provided an electrode comprising:
[0207] a current collector; and
[0208] An electrode material layer is provided on one or both surfaces of a current collector and is formed of the electrode mixture according to any one of the first aspect to the thirteenth aspect.
[0209] <15> According to a fifteenth aspect of the present invention, there is provided a secondary battery including the electrode according to the fourteenth aspect.
[0210] Example
[0211] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to these examples.
[0212] Each numerical value in the examples was measured by the following method.
[0213] (Composition of fluorinated polymer)
[0214] The composition of the fluorinated polymer was measured by solution NMR.
[0215] Measuring device: Varian VNMRS400
[0216] Resonance frequency: 376.04 (Sfrq)
[0217] Pulse width: 30° (pw=6.8)
[0218] (Content of acrylic acid units in fluorinated polymer)
[0219] The content of acrylic acid units in the fluoropolymer is determined by acid-base titration of carboxyl groups. Specifically, about 0.5 g of the fluoropolymer is dissolved in acetone at a temperature of 70°C to 80°C. In order to avoid solidification of the fluoropolymer, 5 ml of water is added dropwise under vigorous stirring. With a neutral transition at about -270 mV, titration is performed using an aqueous NaOH solution with a concentration of 0.1 N until the acidity is completely neutralized. The amount of acrylic acid units contained in 1 g of the fluoropolymer is determined from the measurement results, and the content of acrylic acid units is calculated.
[0220] (Weight average molecular weight)
[0221] The measurement was performed by gel permeation chromatography (GPC). HLC-8320GPC and columns (three SuperAWM-H connected in series) manufactured by Tosoh Corporation were used, dimethylformamide (DMF) as a solvent was allowed to flow at a flow rate of 0.3 ml / min, and the weight average molecular weight was calculated from the measured data (reference: polystyrene).
[0222] (Viscosity)
[0223] The viscosity of the positive electrode mixture was measured using a B-type viscometer (TV-10M manufactured by Toki Sangyo Co., Ltd.) at 25°C, 0.2% humidity, rotor No. M4, and 6 rpm. The measured value after 10 minutes from the start of the measurement was taken as the viscosity.
[0224] (Viscosity change rate)
[0225] The viscosity of the mixture at the time of preparation (η0) and the viscosity 48 hours after preparation (ηn) were measured, and the viscosity change rate (Xn) was calculated by the following formula.
[0226] Xn=ηn / η0×100[%]
[0227] (Peel strength between the positive electrode material layer and the positive electrode current collector)
[0228] Cut the positive electrode to make a 1.2 cm × 7.0 cm test piece. Fix the positive electrode material layer side of the test piece to a movable fixture with double-sided tape, stick the tape on the surface of the positive electrode collector, stretch the tape along 90 degrees at a speed of 100 mm / min, and measure the stress (N / cm) at this time using Autograph. The force sensor of Autograph uses 50N.
[0229] In Examples and Comparative Examples, the following polymers were used as the binder (A).
[0230] Fluoropolymer (AI): Polyvinylidene fluoride
[0231] VdF = 100 (mol%)
[0232] Weight average molecular weight: 900000
[0233] Fluoropolymer (A-II): Polyvinylidene fluoride
[0234] VdF = 100 (mol%)
[0235] Weight average molecular weight: 1800000
[0236] Fluoropolymer (A-III): Polyvinylidene fluoride containing acrylic acid units
[0237] VdF / acrylic acid=99 / 1 (mol%)
[0238] Weight average molecular weight; 1000000
[0239] Fluoropolymer (A-IV): VdF / TFE copolymer
[0240] VdF / TFE=80 / 20 (mol%)
[0241] Weight average molecular weight: 1000000
[0242] Fluoropolymer (AV): VdF / HFP copolymer
[0243] VdF / HFP=94.5 / 5.5
[0244] Weight average molecular weight: 600000
[0245] Fluoropolymer (A-VI): VdF / CTFE copolymer
[0246] VdF / CTFE=97.6 / 2.4
[0247] Weight average molecular weight: 800000
[0248] Other materials used in Examples and Comparative Examples are as follows.
[0249] Positive active material (B)
[0250] NMC811:LiNi 0.8 Mn 0.1 Co 0.1 O 2
[0251] Additives (C)
[0252] tartaric acid
[0253] Polyacrylic acid (PAA) (molecular weight Mn = 250000)
[0254] Conductive agent
[0255] Carbon black (SuperP Li, manufactured by Imerys)
[0256] Examples 1 to 11, Comparative Examples 1 to 8
[0257] The binder (A) is dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a solution of the binder (A) with a concentration of 8% by mass. The solution of the binder (A), the positive electrode active material (B), the additive (C) and the conductive agent are mixed to prepare a positive electrode mixture. The amount of each component used and the solid content concentration of the positive electrode mixture are shown in Tables 1 and 2. The viscosity of the obtained positive electrode mixture is measured and the viscosity change rate is calculated. The results are shown in Tables 1 and 2.
[0258] (Production of positive electrode)
[0259] The obtained positive electrode mixture was evenly coated on one side of the positive electrode collector (aluminum foil with a thickness of 20 μm), dried at 120°C for 60 minutes to completely volatilize the NMP, and then pressed using a roller press with a pressure of 10 tons to produce a positive electrode having a positive electrode material layer on one side of the positive electrode collector. The coating amount of the positive electrode mixture was 22.5 mg / cm 2 The density of the positive electrode material layer is 3.4 g / cm 2 The obtained positive electrode was used to measure the peel strength between the positive electrode material layer and the positive electrode current collector. The results are shown in Tables 1 and 2.
[0260]
[0261]
Claims
1. An electrode mixture, comprising a binder (A), an electrode active material (B) and an additive (C), wherein: The binder (A) comprises a fluorine-containing polymer containing vinylidene fluoride units, The additive (C) comprises a polycarboxylic acid (C1) and a non-fluorine-containing polymer (C2) containing an unsaturated monocarboxylic acid unit.
2. The electrode mixture according to claim 1, wherein The polycarboxylic acid (C1) is at least one selected from the group consisting of tartaric acid, citric acid, oxalic acid, malonic acid, maleic acid, citraconic acid, succinic acid, adipic acid, phthalic acid, isophthalic acid, and terephthalic acid.
3. The electrode mixture according to claim 1 or 2, wherein: The polycarboxylic acid (C1) is tartaric acid.
4. The electrode mixture according to any one of claims 1 to 3, wherein The unsaturated monocarboxylic acid unit is a unit based on a monomer (C2) represented by the general formula (C2), General formula (C2): [Chemistry 6] In the formula, R 1 , R 2 and R 3 Each is independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms; X is an atomic group having a molecular weight of 500 or less and having a single bond or a main chain composed of 1 to 20 atoms; and Y is an inorganic cation and / or an organic cation.
5. The electrode mixture according to any one of claims 1 to 4, wherein The non-fluorinated polymer (C2) is polyacrylic acid.
6. The electrode mixture according to any one of claims 1 to 5, wherein The content of the additive (C) is 0.01% by mass to 5.0% by mass based on the mass of the binder (A) and the electrode active material (B).
7. The electrode mixture according to any one of claims 1 to 6, wherein The mass ratio (C1) / (C2) of the polycarboxylic acid (C1) to the non-fluorinated polymer (C2) is 9 / 91 to 91 / 9.
8. The electrode mixture according to any one of claims 1 to 7, wherein The binder (A) contains polyvinylidene fluoride containing 98.0 mol % or more of vinylidene fluoride units as a fluorine-containing polymer.
9. The electrode mixture according to claim 8, wherein The polyvinylidene fluoride is at least one selected from the group consisting of a fluorinated polymer consisting only of a vinylidene fluoride unit, a fluorinated polymer containing a vinylidene fluoride unit and a fluorinated monomer unit, and a fluorinated polymer containing a vinylidene fluoride unit and a unit based on a monomer (A1) represented by the general formula (A1), wherein the fluorinated monomer unit does not contain a vinylidene fluoride unit, General formula (A1): [Chemistry 7] In the formula, R 1 , R 2 and R 3 Each is independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms; X is an atomic group having a molecular weight of 500 or less and having a single bond or a main chain composed of 1 to 20 atoms; and Y is an inorganic cation and / or an organic cation.
10. The electrode mixture according to claim 8 or 9, wherein The binder (A) further comprises a fluorine-containing copolymer containing less than 98.0 mol % of vinylidene fluoride units.
11. The electrode mixture according to claim 10, wherein The fluorinated copolymer is a fluorinated copolymer containing a vinylidene fluoride unit and a fluorinated monomer unit, wherein the fluorinated monomer unit is at least one selected from the group consisting of a tetrafluoroethylene unit, a hexafluoropropylene unit, a fluoroalkyl vinyl ether unit, a chlorotrifluoroethylene unit and a 2,3,3,3-tetrafluoropropylene unit, wherein the fluorinated monomer unit does not include a vinylidene fluoride unit.
12. The electrode mixture according to any one of claims 1 to 11, wherein The electrode active material (B) contains a lithium composite oxide.
13. The electrode mixture according to any one of claims 1 to 12, wherein The electrode active material (B) contains a lithium metal oxide represented by the general formula (B1), General formula (B1): LiNi Z M (1-Z) O2 In the formula, z satisfies 0.5≤z<1, and M is at least one selected from the group consisting of Co, Mn, and Al.
14. An electrode comprising: a current collector; and An electrode material layer, which is provided on one or both surfaces of a current collector and is formed of the electrode mixture according to any one of claims 1 to 13. 15 . A secondary battery comprising the electrode according to claim 14 .
Citation Information
Patent Citations
Positive electrode mixture for nonaqueous battery and positive electrode structure
WO2009063907A1
Electrode mixture slurry for lithium secondary batteries, and electrode and lithium secondary battery that use said slurry
WO2010092977A1